2022
DOI: 10.26434/chemrxiv-2022-f529m
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selectivity and Efficiency of the Ligation of The Pyrene:Abasic Base Pair by T4 DNA Ligase: Towards Abasic Lesion Detection by Ligation

Abstract: Remarkable selectivity was observed in the ligation of 5’-phosphate 1-pyrene nucleotide terminated strands across from an abasic lesion in a DNA-templated ligation reaction by two different ligase suggesting that pyrene-terminated strands could be used in abasic site detection. This selectivity is significantly greater than other reported unnatural base pairs at the same position revealing the unique properties of the abasic:pyrene pair.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…When a double-clicked sgRNA without stabilizing modifications was used, sgRNA 0 5′ -0 3′ , we did not observe any change in the GFP expression (Figure C). Our previous work found that our double-clicked sgRNA were active in in vitro cutting assays against HPRT and other targets, including Siglec-3, indicating that the double-clicked guides could be used to target different genes. Additionally, as mentioned, with Cas-9-expressing cells we also observed INDELS formation in two targeted genes (EMX1 and WAS) using the corresponding double-clicked sgRNA without stabilizing modifications .…”
Section: Resultsmentioning
confidence: 87%
“…When a double-clicked sgRNA without stabilizing modifications was used, sgRNA 0 5′ -0 3′ , we did not observe any change in the GFP expression (Figure C). Our previous work found that our double-clicked sgRNA were active in in vitro cutting assays against HPRT and other targets, including Siglec-3, indicating that the double-clicked guides could be used to target different genes. Additionally, as mentioned, with Cas-9-expressing cells we also observed INDELS formation in two targeted genes (EMX1 and WAS) using the corresponding double-clicked sgRNA without stabilizing modifications .…”
Section: Resultsmentioning
confidence: 87%